An everyday glimpse of the nation: NHK's morning drama (asadora) and rituality. Issue 2 (1st August 2019) - Scherer, Elisabeth
NHK's morning drama (asadora) has been an important institution on Japanese television since the 1960s and is also known as 'national drama'. This article discusses this media format in the context of rituals and nationhood: watching asadora has become an everyday ritual that can convey a sense of national unity, and the series functions as a 'media ritual' that naturalizes the concept of the Japanese nation, thereby also strengthening the symbolic power of the public broadcaster NHK. As the example of Hiyokko (2017) shows, the producers of this series evoke collective memory and nostalgia by depicting everyday culture and large, nationally charged events such as the 1964 Olympic Games. Reflecting on asadora can shed light on the political and ideological dimensions of seemingly 'banal' media products as well as provide more general insights into the development of television in times of social media and the disappearance of the 'national' TV audience.